THE UNIFICATION CHURCH: A KALEIDOSCOPIC INTRODUCTION - BARKER, EILEEN (Society Register, 2018)
The Unification Church, or the Unificationism, also known as HAS-UWC (Holy Spirit Association for the Unification of World Christianity) or ‘Moonies’ (the term deemed now as disrespectful) but originating from the name of the founder Sun Myung Moon, who set up this Christian religious movement in Northern Korea in 1954 has approximately 3 million followers worldwide. Its existence and popularity are a global phenomenon, interesting not only for sociologists of religion but for politicians, philosophers and people of faith. The impact of this movement and the two-way social change remain a rare subject of study and this paper aims to fill the gaps and to discuss contemporary situation in regards to its followers.